Enhanced HIFU Theranostics with Dual-Frequency-Ring Focused Ultrasound and Activatable Perfluoropentane-Loaded Polymer Nanoparticles - Junjie Chen (MDPI AG, 2021)
High-intensity focused ultrasound (HIFU) has been widely used in tumor ablation in clinical settings. Meanwhile, there is great potential to increase the therapeutic efficiency of temporary cavitation due to enhanced thermal effects and combined mechanical effects from nonlinear vibration and collapse of the microbubbles. In this study, dual-frequency (1.1 and 5 MHz) HIFU was used to produce acoustic droplet vaporization (ADV) microbubbles from activatable perfluoropentane-loaded polymer nanoparticles (PFP@Polymer NPs), which increased the therapeutic outcome of the HIFU and helped realize tumor theranostics with ultrasound contrast imaging. Combined with PFP@Polymer NPs, dual-frequency HIFU changed the shape of the damage lesion and reduced the acoustic intensity threshold of thermal damage significantly, from 216.86 to 62.38 W/cm2. It produced a nearly 20 °C temperature increase in half the irradiation time and exhibited a higher tumor inhibition rate (84.5% ± 3.4%) at a low acoustic intensity (1.1 MHz: 23.77 W/cm2; 5 MHz: 0.35 W/cm2) in vitro than the single-frequency HIFU (60.2% ± 11.9%). Moreover, compared with the traditional PFP@BSA NDs, PFP@Polymer NPs showed higher anti-tumor efficacy (81.13% vs. 69.34%; * p < 0.05) and better contrast-enhanced ultrasound (CEUS) imaging ability (gray value of 57.53 vs. 30.67; **** p < 0.0001), probably benefitting from its uniform and stable structure. It showed potential as a highly efficient tumor theranostics approach based on dual-frequency HIFU and activatable PFP@Polymer NPs.